(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
VacZineNations! is a collaborative artwork led by Rachelle Viader Knowles and Mkrtich Tonoyan, produced by artists, students, and designers in the UK, Canada, China, and Armenia, and exhibited as part of <Immune Nations> at Galleri KiT in Trondheim, Norway, and UNAIDS in Geneva, Switzerland in 2017. This paper positions the artwork within the context of practice-led research and dialogic approaches to art-making, identifying a set of nine key characteristics for translocal, dialogue-based art.